ANALYSIS OF THE EFFECT OF ROA AND ROE ON PER AND ITS IMPLICATIONS ON LQ45 COMPANY SHARE PRICES FOR THE 2009-2019 PERIOD - Manik, Cornelia Dumarya; Ludvy, Achmad (Yayasan Education and Social Center, 2022)
On the Share Price of the company LQ45 either partially or simultaneously in the last 11 (eleven) years from 2009-2019. The purpose of this study is to find out how the Return On Assets (ROA), Return On Equity (ROE) and Price Earning Ratio (PER) in the LQ45 Company, to determine the development of the LQ45 Company's stock price and to determine the effect of ROA and ROE on PER and their implications. The research conducted by the author is descriptive quantitative, namely achieving a discussion of the problems faced by the company on the company's performance in terms of finance. To determine whether or not there is an influence between ROA and ROE on PER and its implications for the LQ45 company's stock price, panel data regression analysis and hypothesis testing regarding the relationship are partially and simultaneously. The results of this study indicate that the partial test results ROA has no significant effect on PER, and ROE has a negative and significant impact on PER. Simultaneous test results show that ROA and ROE positively and significantly impact PER. The following test results also show that PER has a positive and significant impact on the stock price of LQ45 companies for the 2009-2019 period